Innovative Event Management Platform Design with Integrated Ticketing and Networking Features - Putri Feliza, Devina Syilva; Ammadienta, Majestin; Ginasta, Nava Gia (Journal of Digital Business and Innovation Management, 2024)
University of Logistics and International Business (ULBI) by using ticketing features and integrated networks. The focus is on enhancing the efficiency of event planning and execution within the ULBI campus environment, as well as improving participation and transparency. Ticketing features are integrated to synchronize timing and facilitate participant access, while an integrated network is implemented to enhance communication and reduce barriers during planning. By employing software design methodology and action research, this study analyses user needs, expectations, and designs ticketing features and integrated networks. It is hoped that this design will significantly contribute to improving event management within the campus environment, creating a platform that is not only efficient but also capable of enhancing student engagement and information transparency. In conclusion, this proposal provides a foundation for designing technology that can enhance event management at ULBI campus.